2021
DOI: 10.1111/desc.13203
|View full text |Cite
|
Sign up to set email alerts
|

High quality social environment buffers infants’ cognitive development from poor maternal mental health: Evidence from a study in Bhutan

Abstract: Poor maternal mental health negatively impacts cognitive development from infancy to childhood, affecting both behavior and brain architecture. In a non-western context (Thimphu, Bhutan), we demonstrate that culturally-moderated factors such as family, community social support, and enrichment may buffer and scaffold the development of infant cognition when maternal mental health is poor. We used eye-tracking to measure early building blocks of cognition: attention regulation and social perception, in 9-month-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 78 publications
(120 reference statements)
1
6
0
Order By: Relevance
“…information on whether this includes siblings, grandparents, aunts and uncles, etc.) would aid in the interpretation of these results, this finding has to some extent been supported in the literature, where family and social support has been shown to be protective of child and infant cognition (Juvrud et al, 2022;Sonuga-Barke & Mistry, 2000;Taylor et al, 2015). Also, for example, large population-based longitudinal studies in Australia found that a small family was a significant predictor of internalising behaviours in preschool children (Bayer et al, 2008(Bayer et al, , 2012Symeonides et al, 2021), which is in keeping with our results.…”
Section: Cohort 1 (Leap)supporting
confidence: 91%
“…information on whether this includes siblings, grandparents, aunts and uncles, etc.) would aid in the interpretation of these results, this finding has to some extent been supported in the literature, where family and social support has been shown to be protective of child and infant cognition (Juvrud et al, 2022;Sonuga-Barke & Mistry, 2000;Taylor et al, 2015). Also, for example, large population-based longitudinal studies in Australia found that a small family was a significant predictor of internalising behaviours in preschool children (Bayer et al, 2008(Bayer et al, , 2012Symeonides et al, 2021), which is in keeping with our results.…”
Section: Cohort 1 (Leap)supporting
confidence: 91%
“…This may be that larger families provide additional support to a child and protect against these symptoms. Whilst more granular data (e.g., information on whether this includes siblings, grandparents, aunts and uncles etc) would aid in the interpretation of these results, this finding has to some extent been supported in the literature, where family and social support has been shown to be protective of child and infant cognition (Juvrud et al, 2021;Sonuga-Barke & Mistry, 2000;Taylor et al, 2015). Also, for example, large population-based longitudinal studies in Australia found that a small family was a significant predictor of internalising behaviours in preschool children (Bayer et al, 2008(Bayer et al, , 2012Symeonides et al, 2021), which is in keeping with our results.…”
Section: Cohort 1 (Leap)mentioning
confidence: 77%
“…In cases where such conditions exist, they can affect the developmental outcomes of the foetus in many direct ways, such as interrupting the bonding process between mother and baby, breastfeeding, and changes in the cognitive ability of the baby (Smith et al 2022;Juvrud et al 2021). Notwithstanding these factors, pregnant women and single parents from low-income households in the Caribbean may suffer from higher rates of MMH disorders.…”
Section: Maternal Mental Health (Mmh) Costsmentioning
confidence: 99%